(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article draws attention to the directions of genre development of literature in the Ural-Caspian region. The object of the study is the works of one of the writers of the region, the poet-fabulist Amangali Sarkulov, his way of mastering this genre is being studied. The author notes the originality of the poet’s fables style, the author’s research and the peculiarities of his language, his purposeful aspiration to master the genre of fables, satire, continuation of the traditions of his predecessors in this field. At the same time, the article attempts to consider the process of development of the fable genre in the general world literature, to understand the different views, opinions and conclusions of scientists-researchers of this field of literature, the historical periods of the heyday and maturity of the genre, to study and recognize its semantic load. Many peoples have contributed to the formation of the classical genre of fables such as Aesop, Lafontaine and Krylov (traditions and innovation). In particular, the theme of the fables of the poet A. Sarkulov, who adopted the best traditions of the Kazakh fable genre from senior representatives and gave it a new sound, includes complex literary phenomena. The poet describes and exposes the negative phenomena of the modern era and the environment in an allegorical form, endowing the animal and plant world with a stridently living language. The poet’s fables are based on the bitter truth about the society in which we live, the author urges his readers to learn a lesson from the morality of poems and condemn the vices of society. As a result of the literary and scientific analysis of A. Sarkulov’s fables, the authors of the article achieved the substantive, thematic and ideological goals of the study. Keywords: Ural-Caspian region, literary local lore, fable, poetics, genre, allegory.